Energy considerations show that low-barrier hydrogen bonds do not offer a catalytic advantage over ordinary hydrogen bonds - Warshel, Arieh (The National Academy of Sciences of the USA, 1996)
Low-barrier hydrogen bonds have recently been proposed as a major factor in enzyme catalysis. Here we evaluate the feasibility of transition state (TS) stabilization by low-barrier hydrogen bonds in enzymes. Our analysis focuses on the facts that (i) a low-barrier hydrogen bond is less stable than a regular hydrogen bond in water, (ii) TSs are more stable in the enzyme active sites than in water, and (iii) a nonpolar active site would destabilize the TS relative to its energy in water. Combining these points and other experimental and theoretical facts in a physically consistent framework shows that a low-barrier hydrogen bond cannot stabilize the TS more than an ordinary hydrogen bond. The reason for the large catalytic effect of active site hydrogen bonds is that their formation entails a lower reorganization energy than their solution counterparts, due to the preorganized enzyme environment.